THE FEATURES OF OPERATION OF MODERN COMPUTER SIMULATORS - Матвієнко, Роман Михайлович; Сав’юк, Лариса Олександрівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Resulted features of functional structure of the modern computerized trainer complexes, made importance of their development and introduction in the educational process of students of technical specialties